EXPLORING MORPHOLOGICAL FEATURES OF INSTAGRAM CAMPAIGN SLOGANS - Tanalina - Arifah; Testiana Deni Wijayatiningsih; Siti - Sarah; Muhammad Patu DIva Abror; Amara Azmi Addinda Khansa (SIGEH ELT : Journal of Literature and Linguistics, 2026)
This study exploredthe morphological features employed in Instagram campaign slogans and examines how word-formation processes contribute to persuasive digital advertising discourse. Using a quantitative descriptive research design, the study analyzed27 English-language Instagram campaign slogans selected through a rigorous multi-stage sampling process from campaigns published between 2020 and 2023. The slogans were segmented into individual lexical units, yielding 83 analyzable word items, which were systematically coded using a validated morphological coding scheme. The analysis focuses on key word-formation processes, including compounding, derivation, blending, clipping, acronyms, borrowing, and neologism. The findings revealedthat compoundingwas the most dominant morphological process, followed by derivation, indicating a strong preference for compact and semantically rich lexical constructions in Instagram slogans. Less frequent processes such as blending, clipping, and neologism nonetheless playedan important stylistic role by enhancing creativity, brand identity, and platform relevance. The results also show that morphological complexitywas strategically balanced with simple lexical forms to maintain clarity within Instagrams visually driven and text-limited environment. Overall, the study highlightedmorphology as a crucial linguistic resource that supportedbrevity, memorability, and persuasive impact in digital advertising. These findings contributedto linguistic studies on social media discourse and offerredinsights into how word-formation strategieswereoptimized for contemporary marketing communication.